Historiografi Lokal Tragedi Desa Kolam 1965 dan Peran Barisan Tani Indonesia (BTI) dalam Konteks Sosial-Politik Sumatera Utara - Lilis Putri Simamora; Siti Julaiha; Marshal Gilbert Sinambela; Immanuel Steven Limbong; Elianti Napitupulu; Sry Yanti Barus (Medan Resource Center, 2025)
This study examines the local historiography of the 1965 tragedy in Desa Kolam and analyzes the role of Barisan Tani Indonesia (BTI) within the broader socio-political landscape of North Sumatra. Using a qualitative historical method that integrates archival analysis, oral histories, and field observation, the research reconstructs community-level experiences that are largely absent from national narratives of the G30S/PKI period. The findings show that Desa Kolam served as an operational base for BTI prior to the 1965 upheaval, became a site of targeted violence following the state’s designation of the PKI as a prohibited organization, and continues to grapple with collective memory shaped by trauma, silence, and contested interpretations of the past. The study concludes that the micro-history of Desa Kolam offers significant insights into the complexity of political violence in Indonesia and highlights the importance of community-rooted perspectives in enriching the broader historiography of 1965.